Uberground : uma luz sobre a produção cultural uberlandense - Oliveira, Adreana Ivalda de (2021)
This technical-scientific report presents the design and production process of the “Uberground” website which appears with the proposal to present the cultural productions of artists from Uberlândia, native or not, through cultural journalism. The proposal gained a multiplatform configuration due to the advancement and reconfiguration of the means of production and sharing of content through social networks Instagram, Facebook, YouTube and by podcasts. Each of them has its guidelines and the publications must dialogue with them. The website is the benchmark for other platforms because the author has autonomy for writting only according to her editorial line. The author agrees with Raymond Williams with the says that Culture is ordinar” and believes in transformation through art without borders. That is why the focus on local production while dialoguing with global cultures.